Systematic Literature Review of Strategies for Enhancing Sustainable Organizational Performance Practices: the PRISMA Method - Mudiasari, Yunita Reny; Endang Siti Astuti; Afrianty, Tri Wulida (Sekolah Pascasarjana Universitas Brawijaya, 2024)
Over the past few decades, sustainable organizational performance has become a primary focus for organizations and companies. This shift is driven by increasing pressure from stakeholders for companies to prioritize more than just financial profit. Consequently, organizations and companies need to consider sustainable organizational performance. This study uses the PRISMA method to explore the factors influencing sustainable organizational performance (SOP). Additionally, the research seeks to provide valuable insights for practitioners and academics regarding the importance of management strategies that support organizational sustainability. This study employs PRISMA to systematically review the literature in the Scopus and Web of Science databases from the past five years. Relevant studies were screened, evaluated, and analyzed to develop a comprehensive understanding of the factors influencing sustainable organizational performance (SOP). Based on the literature review, five key factors were identified as influencing sustainable organizational performance. These factors are Knowledge Management Practices (KMP), Human Resource Management Practices (HRMP), Organizational Innovation (OI), Organizational Learning (OL), and Organizational Culture (OC). This systematic review provides valuable insights for organizations to consider the factors of knowledge management practices, human resource management practices, organizational innovation, organizational learning, and organizational culture, which can influence sustainable organizational performance Keywords: PRISMA, sustainable organizational performance, systematic literature review